Highly efficient -1st-order reflection in Littrow mounted dielectric double-groove grating - Kota Ito; Hideo Iizuka (AIP Advances, 2013)
We show that in a silicon double-groove grating with two different groove widths per period attached on top of a semi-infinite SiO2 substrate, almost 100% reflectivity is achieved for the -1st-order reflection with an incident angle of 60° in the Littrow mounting condition. The modal analysis reveals that modes propagating in the upward and downward directions have nearly the same amplitudes at resonance. They are added constructively for the -1st-order reflection and destructively for the 0th-order reflection and the -1st-order and 0th-order transmission. The asymmetric structure with a dielectric material poses a unique feature as a four port device.